Pengaruh Produk dan Jasa Agrowisata Serta Teknologi Digital Terhadap Pendapatan Dan Kesejahteraan Petani Nanas Desa Tangkit Baru Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Damhudi, Dedi; Suandi, Suandi; Wahyuni, Ira (Jurnal MeA (Media Agribisnis), 2024)
Agrotourism is an integration of two sectors that support each other holistically, namely the agricultural sector and the tourism sector. It is hoped that by designating a location as agrotourism, regional original income (PAD) will increase, which will be accompanied by an increase in the income of local farmers. Through agrotourism, pineapple gardens are able to make a good contribution to the economy of Tangkit Baru Village, more specifically, pineapple farming income. The aim of this research is to (1). find out the picture of pineapple plantation agrotourism, (2). to determine the level of farmer income and (3) to analyze the factors of agrotourism products and services as well as digital technology that influence the income of pineapple farmers in Tangkit Baru Village. Quantitative research analysis method using the SEM-PLS technique with a sample size of 99 people. The results of the research show that the income level of agrotourism pineapple farmers in Tangkit Baru Village is categorized as high with a monthly income greater than the 2024 Jambi Province UMP, and the community is also on average prosperous as seen from indicators of the level of fulfillment of basic needs, social needs and development needs. Agrotourism products and digital technology has a real significant effect on the income of agrotourism farmers, while agrotourism services have an influence but not significant on the income of agrotourism farmers, because income from agrotourism services is only collected individually, there is no standard governance and rules at agrotourism locations, especially parking services.